PENYULUHAN POLA MAKAN SEHAT DAN PEMERIKSAAN KESEHATAN GUNA MENINGKATKAN KUALITAS HIDUP LANSIA DI CIMAHI SELATAN - Fiorida Mathilda; Patricia Gita Naully (Lembaga Penelitian dan Pengabdian Masyarakat, 2021)
The elderly are a group of people who are vulnerable to degenerative diseases such as hypertension, diabetes mellitus, and others. The causes include a lack of knowledge about healthy diet and the lack of health checks. The purpose of this community service activity is to improve the quality of life of the elderly in Kelurahan Utama of South Cimahi by socializing healthy diets and conducting health checks. Media used for healthy diet counseling are power points, videos, and posters. Health examinations conducted include measurements of body mass index, blood pressure, blood glucose levels, triglycerides, total cholesterol, and uric acid. The results of the health examination showed quite a lot of elderly people who suffer from degenerative diseases. Through this activity, the elderly in Kelurahan Utama of South Cimahi gained knowledge about healthy diet in order to avoid various diseases and know the disease that is being experienced so that they can immediately undergo proper treatment.